Identification of a mutation associated with fatal Foal Immunodeficiency Syndrome in the Fell and Dales pony. - Laura Y Fox-Clipsham; Stuart D Carter; Ian Goodhead; Neil Hall; Derek C Knottenbelt; Paul D F May; William E Ollier; June E Swinburne (PLoS Genetics)
The Fell and Dales are rare native UK pony breeds at risk due to falling numbers, in-breeding, and inherited disease. Specifically, the lethal Mendelian recessive disease Foal Immunodeficiency Syndrome (FIS), which manifests as B-lymphocyte immunodeficiency and progressive anemia, is a substantial threat. A significant percentage (∼10%) of the Fell ponies born each year dies from FIS, compromising the long-term survival of this breed. Moreover, the likely spread of FIS into other breeds is of major concern. Indeed, FIS was identified in the Dales pony, a related breed, during the course of this work. Using a stepwise approach comprising linkage and homozygosity mapping followed by haplotype analysis, we mapped the mutation using 14 FIS-affected, 17 obligate carriers, and 10 adults of unknown carrier status to a ∼1 Mb region (29.8 - 30.8 Mb) on chromosome (ECA) 26. A subsequent genome-wide association study identified two SNPs on ECA26 that showed genome-wide significance after Bonferroni correction for multiple testing: BIEC2-692674 at 29.804 Mb and BIEC2-693138 at 32.19 Mb. The associated region spanned 2.6 Mb from ∼29.6 Mb to 32.2 Mb on ECA26. Re-sequencing of this region identified a mutation in the sodium/myo-inositol cotransporter gene (SLC5A3); this causes a P446L substitution in the protein. This gene plays a crucial role in the regulatory response to osmotic stress that is essential in many tissues including lymphoid tissues and during early embryonic development. We propose that the amino acid substitution we identify here alters the function of SLC5A3, leading to erythropoiesis failure and compromise of the immune system. FIS is of significant biological interest as it is unique and is caused by a gene not previously associated with a mammalian disease. Having identified the associated gene, we are now able to eradicate FIS from equine populations by informed selective breeding.